The 1/N expansion of tensor models with two symmetric tensors - Gurǎu, Rǎzvan (Communications in mathematical physics, 2018)
It is well known that tensor models for a tensor with no symmetry admit a 1/N expansion dominated by melonic graphs. This result relies crucially on identifying jackets, which are globally defined ribbon graphs embedded in the tensor graph. In contrast, no result of this kind has so far been established for symmetric tensors because global jackets do not exist. In this paper we introduce a new approach to the 1/N expansion in tensor models adapted to symmetric tensors. In particular we do not use any global structure like the jackets. We prove that, for any rank D, a tensor model with two symmetric tensors and interactions the complete graph KD+1 admits a 1/N expansion dominated by melonic graphs.
Published online: 15 December 2017
Gesehen am 06.10.2022